Spiritualism Types and Implications of Saudi Arabian Cultural Transmission of Religious Moderation in Indonesia - Basith, Fardan Abdul; Purwandi, Ayi Dini; Erihadiana, Mohamad; Mahmud, Mahmud; Hamdani, Dwi Haryanto; Aziz, Muhammad Ridwan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to systematically examine patterns of spiritualism and the impact of Saudi Arabian religious and cultural transmission on religious moderation in Indonesia through a Systematic Literature Review (SLR). The data consist of secondary qualitative data derived from peer-reviewed journal articles, academic proceedings, scholarly books, and research reports that examine Saudi Arabian religious-cultural influence, Islamic spiritualism, and religious moderation in Indonesia and the broader Asian Muslim context. Data sources were obtained from reputable academic databases, including Scopus, Web of Science, Google Scholar, DOAJ, and Garuda Ministry of Research, Technology, and Higher Education. The selected literature was published between 2019 and 2025 and written in either English or Indonesian. After applying inclusion and exclusion criteria, 30 articles were deemed eligible and used as the primary corpus for analysis. Data collection was conducted through a systematic and multi-stage literature search strategy. Relevant keywords were identified through an initial scoping search and refined using Boolean operators (AND, OR) to enhance search precision. All retrieved publications were managed using reference management software (Mendeley) to organize citations and remove duplicates. Data analysis was performed using thematic synthesis, as developed by Thomas and Harden. The analytical process consisted of three main stages. First, line-by-line coding was applied to extract meaningful units related to cultural transmission, spiritualism, and religious moderation. Second, the initial codes were organized into descriptive themes that reflect recurring patterns across the literature. Third, analytical themes were developed through interpretative synthesis to generate conceptual insights into how Saudi Arabian cultural transmission interacts with local Indonesian socio-religious dynamics. This approach allows the integration of diverse methodological perspectives and facilitates the development of a comprehensive analytical framework that explains the relationship between transnational religious influence and religious moderation in Indonesia.